Empowering students for the future: embedding soft skills into higher education curricula - Pereira, E. R.; Mauritti, R; Oliveira, A.; Wojciechowska, M.; Belchior-Rocha, H. (EDULEARN25 Proceedings, 2025)
Higher education is undergoing a profound transformation, driven by the pressing need to prepare students for an uncertain and rapidly evolving future. In an era where career paths are increasingly fluid, and professional challenges demand continuous adaptation, universities must go beyond the traditional model of segmented knowledge. The integration of transversal subjects - those that cut across disciplinary boundaries - has emerged as a powerful strategy to equip students with essential skills that complement their technical expertise, ensuring they can navigate complex, unpredictable landscapes with confidence. This paper explores the experiences of two universities, one in Portugal and another in Brazil, that have embraced this shift by embedding transversal skills courses within their academic structures. These initiatives aim to cultivate a diverse skill set that extends beyond specialized knowledge, fostering intellectual agility, resilience, and responsible citizenship. The courses encompass a broad spectrum of competencies, including analytical and academic skills such as critical thinking, problem-solving, technical writing, and knowledge application; socio-emotional skills like stress and conflict management, teamwork, and adaptability; and behavioral competencies such as leadership, communication, time management, and sustainable decision-making. By breaking down the rigid barriers between academic disciplines, these programs encourage students to engage in active, participatory learning experiences, fostering a sense of ownership over their educational journey. Organized into interdisciplinary groups, students not only gain exposure to multiple perspectives but also develop the ability to collaborate effectively across different fields. This shift toward an interactive and self-directed approach to learning is essential in preparing them for the realities of a dynamic and interconnected world. More than ever, individuals must be equipped with the capacity to think critically, adapt swiftly, and act responsibly in an environment of continuous change. The cultivation of transversal skills bridges the gap between academic training and real-world challenges, reinforcing students’ ability to approach complexity with confidence and a proactive mindset. By investing in these competencies, universities are shaping engaged, reflective individuals who are ready to face the uncertainties of the future with resilience and purpose.